Role of Oxidative Stress in Varicocele - Wang, Kaixian; Gao, Yuanyuan; Wang, Chen; Liang, Meng; Liao, Yaping; Hu, Ke (Frontiers in Genetics, 2022)
According to the official statistics of the World Health Organization, at least 48 million couples and 186 million people suffer from infertility. Varicocele has been recognized as the leading cause of male infertility and can affect spermatogenesis and cause testicular and epididymal disorders through multiple diverse pathophysiological processes. Reactive oxygen species (ROS) produced by oxidative stress have been reconciled as an important pathogenic factor throughout the course of varicocele. Testis respond to heat stress, hypoxia, and inflammation at the cost of producing excessive ROS. High levels of ROS can lead to infertility not only through lipid peroxidation or DNA damage, but also by inactivating enzymes and proteins in spermatogenesis. This review studies the oxidative stress and its role in the pathophysiology and molecular biology of varicocele in the context of a decline in fertility.